Toxicity of extract seeds custard apple (Annona squamosa) on mortality of mosquito larvae Anopheles sp. - Ristiati, Ni Putu; Dewi, Ni Putu Sri Ratna; Mulyadiharja, Sanusi; Prastuti, Ni Wayan Gunia (Jurnal Biologi Udayana; Vol 23 No 1 (2019): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2019.v23.i01.p01, 2019)
The aimed of this study were to determine differences of toxicity of custard apple seeds extract at different concentrations on mortality the mosquito larvae of Anopheles sp. and to find the most effective concentration of extract towards the mosquitoes’ mortality. The experiment used Randomised Complete Design. The samples used were instar larvae of Anopheles sp. The crude extracts were obtained through maceration process. The research was conducted for 48 hours at Laboratory of Biology Department of Undiksha. Data were analysed using one way anava. The results showed that there were significant differences in which the value of f count > f table (16.500>2.87).  It showed different concentration of toxicity from custard apple seeds extract on mortality mosquito larvae of Anopheles sp.  The concentration of the extract was linier to the mortality of the Anopheles sp. The most effective concentration extract as a larvacide was 50 ppm.